Photocatalyzed Transition‐Metal‐Free Oxidative Cross‐Coupling Reactions of Tetraorganoborates. Issue 13 (3rd February 2021) - Music, Arif; Baumann, Andreas N.; Boser, Florian; Müller, Nicolas; Matz, Florian; Jagau, Thomas C.; Didier, Dorian
Abstract: Readily accessible tetraorganoborate salts undergo selective coupling reactions under blue light irradiation in the presence of catalytic amounts of transition‐metal‐free acridinium photocatalysts to furnish unsymmetrical biaryls, heterobiaryls and arylated olefins. This represents an interesting conceptual approach to forge C−C bonds between aryl, heteroaryl and alkenyl groups under smooth photochemical conditions. Computational studies were conducted to investigate the mechanism of the transformation. Abstract : Shining light on organoborates : A photocatalyzed oxidative cross‐coupling reaction of functionalized organoborates is described, providing a diverse range of biaryl and olefin products. The mechanism of this C−C bond formation was investigated through quantum chemical calculations, revealing an unusual boracyclic intermediate.